Decoding trust: How transparency, political stability, and leadership shape public confidence in government institutions - Eaosinsup, Duangruedee; Kulachai , Waiphot (วารสารการบริหาร การจัดการ และการพัฒนาที่ยั่งยืน, 2025)
This study explores how transparency, political stability, and leadership influence public trust in government institutions through a qualitative approach involving in-depth interviews with 17 diverse key informants. Utilizing thematic analysis and NVivo tools, the research identifies critical themes that highlight the nuanced dynamics of trust-building in governance. Findings reveal that transparency enhances trust by promoting accountability and reducing corruption perceptions; however, excessive transparency without effective communication may lead to confusion and diminished trust. Political stability contributes to institutional confidence through consistent governance and problem-solving, yet excessive stability may result in stagnation if not balanced with adaptability. Leadership emerged as a pivotal factor, demonstrating that ethical and participatory leadership significantly enhances public perception of governance. The study integrates Institutional Trust Theory and Political Legitimacy Theory, proposing a holistic framework where transparency, stability, and leadership interact dynamically to shape public trust. These insights offer valuable guidance for policymakers seeking to strengthen governance by promoting strategic transparency, adaptive stability, and inclusive leadership. Ultimately, this research contributes to the broader academic discourse on governance and trust, offering practical recommendations for building resilient and responsive government institutions that align with societal values and expectations.